2013
DOI: 10.1007/s00246-013-0676-6
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Defibrillators in Young Hypertrophic Cardiomyopathy Patients: A Multicenter Study

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common genetic cardiovascular disease, with an annual risk of sudden cardiac death (SCD) estimated at 1 %. Limited data are available regarding both the risk of SCD in the young HCM population and the use of implantable cardioverter-defibrillators (ICDs). This retrospective study included all patients with HCM who underwent ICD implantation for primary or secondary prevention of SCD before the age of 30 years at five institutions between 1995 and 2009. There were 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…A significant association with SCD was shown in two univariate analyses (p<0.0001 19 , p=0.004 20 ), and one multivariable analysis (p<0.001 20 ). Kamp et al 18 described a small cohort of patients with previous ICD implantation in which a previous AE was not significant for SCD, however this study was underpowered to detect a difference. Decker et al 17 did not find an association with all CVD, however SCD was not analysed separately.…”
Section: Previous Adverse Cardiac Event (Aborted Cardiac Arrest or Sumentioning
confidence: 87%
See 2 more Smart Citations
“…A significant association with SCD was shown in two univariate analyses (p<0.0001 19 , p=0.004 20 ), and one multivariable analysis (p<0.001 20 ). Kamp et al 18 described a small cohort of patients with previous ICD implantation in which a previous AE was not significant for SCD, however this study was underpowered to detect a difference. Decker et al 17 did not find an association with all CVD, however SCD was not analysed separately.…”
Section: Previous Adverse Cardiac Event (Aborted Cardiac Arrest or Sumentioning
confidence: 87%
“…Only one study reported a statistically significant association with SCD (HR 10.6, 95%CI 1.2-90.2, p=0.03) 18 .…”
Section: Family History Of Sudden Cardiac Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…In larger adult studies, the rate of IS has been reported to range from 10% to 15%. 16,25,27 However, most studies of ICD use in pediatric and CHD patients have found rates of IS to be between 20% and 30% in these patient populations, 10,11,13,14,[34][35][36][37][38][39][40] with some studies observing IS in up to 40% to 50% of patients and, in some instances, with inappropriate shocks being more frequent than appropriate shocks. 12,19,41,42 This is likely a result of a more active lifestyle, faster rates of sinus tachycardia, longer duration of implantation, smaller patient size, and a higher rate of device and lead complications relative to adult patients.…”
Section: Device Therapymentioning
confidence: 99%
“…The use of antiarrhythmic medication has not been conclusively demonstrated to reduce the level of shock burden in this population, despite the common practice of altering medical management in patients who receive shocks. 36 However, the high baseline rate of antiarrhythmic medication use makes this a difficult association to find in the absence of a randomized trial.…”
Section: Non-device-based Interventionsmentioning
confidence: 99%